CRISPR Cas9 in Pancreatic Cancer Research - Yang, Hai; Bailey, Peter; Pilarsky, Christian (Frontiers in Cell and Developmental Biology, 2019)
Pancreatic cancer is one of the most common and fatal cancer. The poor prognosis of pancreatic cancer has not significant improved in the past decades. The main treatments for pancreatic are surgery, radiation therapy and chemotherapy, but there is also a lot of efforts to improve treatments. In recent year, CRISPR/Cas9 technology become one of the most famous and powerful gene editing tools, and has been applied in pancreatic cancer research. It has great potential for scientific research and clinical treatment in pancreatic cancer. In this review, we summarize currently application of CRISPR/Cas9 technology in pancreatic cancer research, and also highlight the potential vulnerable target genes in pancreatic cancer.